2013
DOI: 10.1039/c3ra44564j
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic one-step synthesis of Pt-decorated few-layer graphenes

Abstract: This study presents the influence of the various reaction parameters (catalyst concentration, reaction temperature, hydrocarbon flow rate, and reaction time) on the one-step growth of few-layer graphenes decorated with metallic platinum (Pt) nanoparticles. The latter were synthesized over a Pt/MgO catalyst using radio-frequency catalytic chemical vapor deposition (CCVD) from methane. A mixture of nanotubes and graphenes in various ratios was produced depending on the synthesis conditions. The nanotubes have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…The FT-IR and XPS data presented in our previous works [9][10][11] showed that cCVD graphene are clean carbon honeycomb surfaces, while the chemically obtained nanocomposites posses some residual functional groups that can be involved in the sensing mechanism. A special case is represented by the N-Gr (Figs.…”
Section: Sensing Propertiesmentioning
confidence: 98%
See 3 more Smart Citations
“…The FT-IR and XPS data presented in our previous works [9][10][11] showed that cCVD graphene are clean carbon honeycomb surfaces, while the chemically obtained nanocomposites posses some residual functional groups that can be involved in the sensing mechanism. A special case is represented by the N-Gr (Figs.…”
Section: Sensing Propertiesmentioning
confidence: 98%
“…The synthesis and TEM characterization of few-layer graphene with various metallic nanoparticles (Gr-Au, Gr-Ag, Gr-Pt,) was previously reported (Scheme 2) [9][10][11].…”
Section: Synthesis and Morphological Characterization Of Graphene Nanmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 Briey, the two samples were prepared by catalytic Chemical Vapor Deposition with Induction Heating (cCVD-IH) using the corresponding mixed catalyst (Au x /MgO and Pt x /MgO, where…”
Section: Preparation Of Graphene-metal Nanoparticles Compositesmentioning
confidence: 99%